Music on the edge: Busking at the Cliffs of Moher and the commodification of a musical landscape. (April 2014) - Kaul, Adam
The Cliffs of Moher is one of the most popular tourist sites in all of Ireland, and buskers have been playing traditional music there for generations. The site and traditional music have each become powerful metonyms for Irish identity. In this article, I explore the complex and changing relationship between Irish identity, music, and tourism at the cliffs. In particular, I analyze recent conflicts that have erupted between musicians and the local tourism authorities which opened a €32 million award-winning interpretive center there in 2007.